Case report: Central venous catheter thrombosis complicated by chronic thromboembolic disease/pulmonary hypertension in two children requiring parenteral nutrition - Hanuna, Maja; Pattathu, Joseph; Buech, Joscha; Kamla, Christine; Kneidinger, Nikolaus; Behr, Juergen; Milger, Katrin; Veit, Tobias; Nagel, Marina; Abicht, Jan; Dalla-Pozza, Robert; Fischer, Marcus; et al. (Frontiers in Cardiovascular Medicine, 2023)
Chronic thromboembolic pulmonary hypertension is a rare but life-threatening complication of long-term central venous catheters (CVC) in children. However, evidence in terms of potential treatment strategies and outcome data remains scarce. We describe two cases of CVC-related thrombosis (Hickman-catheter) complicated by recurrent pulmonary emboli. One patient experienced a complete thromboembolic obstruction of the right pulmonary artery with normal pulmonary pressures and the second patient suffered from a central thromboembolic obstruction of both pulmonary arteries associated with severe pulmonary hypertension. Both patients successfully underwent surgical thromboendarterectomy with deep hypothermic circulatory arrest.